Safety and Immunogenicity of a 2-Dose Heterologous Vaccine Regimen With Ad26.ZEBOV and MVA-BN-Filo Ebola Vaccines: 12-Month Data From a Phase 1 Randomized Clinical Trial in Nairobi, Kenya - Mutua, Gaudensia (J Infect Dis, 2019)
BACKGROUND: During the 2014 West African Ebola outbreak, Ebola vaccine development was accelerated. The phase 1 VAC52150EBL1003 study was performed to investigate 2-dose heterologous vaccination with Ad26.ZEBOV and MVA-BN-Filo in an African population located in a high-altitude setting in Nairobi, Kenya. METHODS: Healthy adult volunteers were randomized to receive one of four 2-dose vaccination schedules. The first vaccination was administered at baseline (Ad26.ZEBOV or MVA-BN-Filo), followed by the second vaccination with the alternate vaccine after either 28 or 56 days. Each schedule had a placebo comparator group. The primary objective was to assess the safety and tolerability of these regimens. RESULTS: Seventy-two volunteers were randomized into 4 groups of 18 (15 received vaccine, and 3 received placebo). The most frequent solicited systemic adverse event was headache (frequency, 50%, 61%, and 42% per dose for MVA-BN-Filo, Ad26.ZEBOV, and placebo, respectively). The most frequent solicited local AE was injection site pain (frequency, 78%, 63%, and 33% per dose for MVA-BN-Filo, Ad26.ZEBOV, and placebo, respectively). No differences in adverse events were observed among the different vaccine regimens. High levels of binding and neutralizing anti–Ebola virus glycoprotein antibodies were induced by all regimens and sustained to day 360 after the first dose. CONCLUSIONS: Two-dose heterologous vaccination with Ad26.ZEBOV and MVA-BN-Filo was well tolerated and highly immunogenic against Ebola virus glycoprotein. CLINICAL TRIALS REGISTRATION: NCT02376426